Potentials of Chitosan-Based Delivery Systems in Wound Therapy: Bioadhesion Study - Julia Hurler; Nataša Škalko-Basnet (Journal of Functional Biomaterials, 2012)
Chitosan is currently proposed to be one of the most promising polymers in wound dressing development. Our research focuses on its potential as a vehicle for nano-delivery systems destined for burn therapy. One of the most important features of wound dressing is its bioadhesion to the wounded site. We compared the bioadhesive properties of chitosan with those of Carbopol, a synthetic origin polymer. Chitosan-based hydrogels of different molecular weights were first analyzed by texture analysis for gel cohesiveness, adhesiveness and hardness. In vitro release studies showed no difference in release of model antimicrobial drug from the different hydrogel formulations. Bioadhesion tests were performed on pig ear skin and the detachment force, necessary to remove the die from the skin, and the amount of remaining formulation on the skin were determined. Although no significant difference regarding detachment force could be seen between Carbopol-based and chitosan-based formulations, almost double the amount of chitosan formulation remained on the skin as compared to Carbopol formulations. The findings confirmed the great potential of chitosan-based delivery systems in advanced wound therapy. Moreover, results suggest that formulation retention on the ex vivo skin samples could provide deeper insight on formulation bioadhesiveness than the determination of detachment force.